PENCEGAHAN PEMBAJAKAN ATLET E-SPORTS MELALUI PERLINDUNGAN HUKUM KEPADA TIM E-SPORTS - Maulidea, Cantika; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
E-sports is a modern sport that is currently quite popular and promising in Indonesia. In competitive sports, unsupportive things often happen, one of which is poaching. Poaching is considered unsupportive because it can cause losses to E-sports teams whose athletes are illegally captured. Because of this, there needs to be legal protection to limit the actions of the parties involved in the E-sports ecosystem. This research uses normative legal research methods as a method to find out what are the legal consequences of the existence of poaching and to analyze how forms of legal protection can be applied to E-sports teams as a form of prevention or rule over poaching practices. The results of this study found that the result of the poaching was the emergence of sanctions in the form of compensation, and legal efforts to protect the E-sports team from the poaching are through PBESI regulations and the arrangement of specific clauses in employment agreement contracts